Relações de gênero na educação física escolar: uma abordagem interventiva a partir do currículo do Estado de São Paulo x percepção dos(as) estudantes - COCATO, Zirleide (2019)
This dissertation is linked to the Graduate Program in Education of the University of Oeste Paulista, the research line Public Policies in Education, Educational Practices and Diversity and the research group State, Educational Policies and Democracy (EPED). Although the issue of gender relations has gained greater visibility with regard to scientific production, especially in recent years, there has been great resistance from some groups in society, so that this theme can be addressed in school education. The research assumed as a central objective, identify and analyze the interfaces of the Physical Education curriculum of the state of São Paulo with gender issues and how they are understood by high school students from interventions on the subject. The theoretical perspective adopted focused on gender studies and the contributions of critical studies, with a historical-cultural focus on Physical Education. The qualitative research used interventional research and document analysis to obtain the data. The participants were students from a 3rd grade high school class from a state school in a medium-sized city of São Paulo state. In the first moment, the documentary analysis of the student and teacher notebooks linked to the Physical Education curriculum of the São Paulo state was carried out in order to identify the learning situations present in the referred that address the gender issues and how they are proposals. Subsequently, a questionnaire with open and closed questions was applied to identify students' initial perceptions of the topic. Afterwards, the theme “gender” was mediated with the students of the 3rd grade of high school as part of the intervention developed, through a set of six classes, in which the activities proposed in the learning situations of the teacher's notebook were deepened referring to the gender theme. Finally, after the interventions, a focus group with seven students was conducted to investigate how they conceived gender relations based on experiences and reflections on the manifestations of body culture in Physical Education classes. The collected data were analyzed through data triangulation and revealed that the treatment with the gender theme in the Physical Education curriculum of the state of São Paulo is timid; that the segregation of the contents of the body cultural manifestation is still present in the students' perceptions and that there is an urgency to intentionally and scientifically problematize gender issues.